75As NQR signature of the isoelectronic nature of ruthenium for iron substitution in LaFe1−xRuxAsO. Issue 5 (16th February 2014) - Mazzani, Marcello; Bonfà, Pietro; Allodi, Giuseppe; Sanna, Samuele; Martinelli, Alberto; Palenzona, Andrea; Manfrinetti, Pietro; Putti, Marina; De Renzi, Roberto
<x xml:space="preserve">Abstract</x> We have investigated the effects of the isovalent ruthenium substitution in LaFe<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh5js0t6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1−x</alternatives>Ru<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh5js18x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />x</alternatives>AsO, by extensive 75As NQR (nuclear quadrupole resonance) measurements, supported by DFT (density functional theory) calculations, in order to characterize both the lattice and electronic structure details. The evidence for five different local configurations around the arsenic site emerges upon increasing ruthenium for iron substitution. DFT calculations confirm the attribution of the measured electric field gradients (EFGs) to ruthenium atom occupancies (0, 1, 2, 3, and 4) on the nearest‐neighbour sites of arsenic. It is found that the low‐frequency (Ru‐free) NQR peak remains almost unaffected upon ruthenium substitution, providing an experimental confirmation that ruthenium does not introduce delocalized carriers in the iron plane.